Effect of tragacanth gum (Astragalus gummifer) and melaleuca essential oil to extend the shelf life of minimally processed pineapples - Almeida, Maiara Mantovani Maciel de; Pizato, Sandriane; Basaglia, Rafaela Rodrigues; Pacco-Huamani, Maria Cecilia; Pinedo, Rosalinda Arévalo; Cortez-Vega, William Renzo (Acta Scientiarum. Technology, 2024)
The consumption of minimally processed fruit is increasing due to its convenience, but its shelf life is reduced when compared to fresh fruit (in natura). The effects of using tragacanth gum (Astragalus gummifer) and melaleuca essential oil (Melaleuca alternifolia) as an edible coating on minimally processed pineapples (Smooth cayenne) were investigated in this study. The pineapples were sanitized, peeled, cut into standardized pieces, and immersed in the toppings, obtaining four treatments: T1 (control); T2 (0.5 tragacanth gum and 0.2% melaleuca essential oil); T3 (0.5 tragacanth gum and 0.3% melaleuca essential oil); T4 (0.5 tragacanth gum and 0.4% melaleuca essential oil), then drained and stored in PET (Polyethylene Terephthalate) containers with a lid, under refrigeration at 5Â±1Â°C for 12 days. Physicochemical and microbiological analyses were performed. The samples T2 and T4 obtained less mass loss and less decrease in total soluble solids content. The T2 sample also showed promising results by reducing the loss of texture and delaying the growth of mold and yeast in relation to the control sample over 12 days of storage. The use of tragacanth gum together with melaleuca essential oil was efficient in maintaining the quality of minimally processed pineapples for a longer time.